Ford show exhibition display (circa 1930s) - Hercules Incorporated (1930)
General view of the Hercules Powder Company display at a Ford Motor Company trade show held in Detroit, Michigan. The display depicts the production of nitrocellulose and its use in a variety of products, including lacquers, safety glass, and coated textiles. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Corporations; Chemical industry; Hercules Powder Company; Trade shows; Advertising; Advertising, Industrial; Nitrocellulose